Purification and Characterization of Lipase from thermophilic Geobacillus sp. - Mehta, Akshita; Kumar Saun, Nitin; Gupta, Reena (Current Biotechnology, 2016)
Background: Thermostable alkaline lipases have commercial value and find applications in various industrial and biotechnological sectors such as additives in detergents and food industries, environmental bioremediations and in molecular biology. To use any lipase for esterification or any other application, it is important to purify and characterize the enzyme and study its properties. The aim of this paper to purify and characterize lipase from thermophilic Geobacillus sp. Methods: Lipase was purified to homogeneity by ammonium salt precipitation and column chromatography i.e. Sepharose column (size 12 × 2 cm) (Sigma Chemicals, USA) and gel filtration chromatography (size 12 × 2 cm) (Sigma Chemicals, USA). The SDS-PAGE was performed on 10% polyacrylamide gel (with 4% stacking gel) using reference molecular weight markers (Genei, Bangalore, India). The purified lipase was further characterized for various parameters. Results: The results revealed that the enzyme was purified to 5.4-fold after Sephacryl S-300 chromatography. The purified lipase showed a single band on a 10% SDS-PAGE and molecular mass of enzyme was found to be 97 kDa. The purified enzyme of Geobacillus sp. exhibited maximum lipolytic activity at temperature 55°C and pH 9.5. The half life of the lipase of Geobacillus sp. at 55°C was found to be 90 min. Conclusion: Lipase produced by Geobacillus sp. is most suitable for industrial applications because of its thermostablity, easier production, relatively inexpensive fermentation techniques and alkaline pH range, which enables its use in organic synthesis applications such as synthesis of esters, biodiesel and flavoured compounds.
Keywords: lipase